Improving Dynamic Update for Operating Systems - Baumann, Andrew; Appavoo, Jonathan (20th ACM Symposium on OS Principles - SOSP ’05, 2005)
Modern operating systems are subject to a constant stream of patches and updates: to fix bugs, improve performance, or add features. Dynamic update offers significantly increased availability for operating systems, and enables administrators to avoid a difficult choice between the cost of down time and the risk of remaining unpatched. However, an operating system kernel is a unique environment for dynamic update; it is generally event-driven, multithreaded, and involves a high degree of concurrency and asynchrony. It also provides a very restricted runtime environment. Existing dynamic update mechanisms are generally unsuited for use with operating-system code, either because they do not support concurrency [11, 13], require the system to be implemented in a specific language [1, 7, 9], or rely on a higher level of runtime support than is feasible within a traditional OS [5, 6]. This work aims at developing a model supporting dynamic update to operating systems code.
Work-in-Progress Session